On the Oscillatory Behavior of Solutions of Second-Order Non-Linear Differential Equations with Damping Term - Mohamed Mazen; Mohamed M. A. El-Sheikh; Samah Euat Tallah; Gamal A. F. Ismail (Mathematics, 2024)
In this paper, we discuss the oscillatory behavior of solutions of two general classes of nonlinear second-order differential equations. New criteria are obtained using Riccati transformations and the integral averaging techniques. The obtained results improve and generalize some recent criteria in the literature. Moreover, a traditional condition is relaxed. Three examples are given to justify the results.